(untitled) - Meriam, J. L. (Hoboken, NJ, 2015)
Dynamics 8th Edition has provided a solid foundation of mechanics principles for more than 60 years. Now in its eighth edition, the text continues to help students develop their problem-solving skills with an extensive variety of engaging problems related to engineering design. In addition to new homework problems, the text includes a number of helpful sample problems. To help students build necessary visualization and problem-solving skills, the text strongly emphasizes drawing free-body diagrams- one of the most important skills needed to solve mechanics problems.
Keywords: Động lực học,Machinery, Dynamics of,Mechanics, applied